Immunoablative therapy followed by autologous hematopoietic stem cell transplantation as the first-line disease-modifying therapy in patients with multiple sclerosis - Lachnit, Martin; Revendova, Kamila Zondra; Hradilek, Pavel; Bunganic, Radovan; Koristek, Zdenek; Jelinek, Tomas; Skutova, Monika; Piza, Radim; Volny, Ondrej; Hajek, Roman; Bar, Michal (Biomedical papers, 2024)
Introduction. Immunoablative therapy followed by autologous hematopoietic stem cell transplantation (AHSCT) is one of the possible disease-modifying therapies (DMTs) for patients with multiple sclerosis (MS). In this case series, we would like to present six patients with MS, who underwent AHSCT as the first-line DMT. Case reports. Six MS patients with a rapid progression of disability with or without relapses underwent AHSCT as the first-line DMT at the University Hospital Ostrava between 2018 and 2021. The conditioning regimens for AHSCT used were a medium-intensity regime BEAM (Carmustine, Etoposid, Cytarabin, Melphalan) and low-intensity regime based on Cyclophosphamide. Four out of six patients showed some disability progression after AHSCT, so the rapid progression of MS was just slowed down by AHSCT. One patient developed activity on magnetic resonance imaging three months after AHSCT, and two experienced mild relapses during the follow-up period. None of our patients developed grade 4 non-hematological toxicity; all infections were mild. In one patient, an allergic reaction probably to dimethyl sulfoxide was observed. Conclusion. Our case series of 6 patients shows that AHSCT is a promising therapeutic approach to slow down the rapid progression of clinical disability in MS patients with a good safety profile.
Keywords: multiple sclerosis; immunoablative therapy; autologous hematopoietic stem cell transplantation